THE INFLUENCE OF THE BLENDED LEARNING MODEL ON CIVICS LEARNING OUTCOMES AT NURUL ISLAM INDONESIA HIGH SCHOOL FOR THE 2022/2023 ACADEMIC YEAR - azwan, Muhammad; Husna, Muhammad Faisal (Media Inovasi Pendidikan dan Publikasi, 2024)
This research is experimental research using the